2007
DOI: 10.1007/s11239-007-0014-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of supplemental vitamin K therapy in patients on oral anticoagulants with unstable international normalized ratios

Abstract: INR fluctuations may decrease in selected patients with unstable INRs who receive vitamin K supplementation. A study with a larger sample size and longer follow-up period is needed. The results of the present study can help design such a study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 5 publications
1
41
0
Order By: Relevance
“…Some have suggested that taking daily vitamin K could decrease the day-to-day variability of blood vitamin K levels and allow for more predictable warfarin dosing and less time out of therapeutic range [23]. Lastly, a few genetic mutations (CYP2C9*2, CYP2C9*3 and VKORC1) have been associated with altered metabolism of warfarin, and changes in clinical response [24].…”
Section: Introductionmentioning
confidence: 99%
“…Some have suggested that taking daily vitamin K could decrease the day-to-day variability of blood vitamin K levels and allow for more predictable warfarin dosing and less time out of therapeutic range [23]. Lastly, a few genetic mutations (CYP2C9*2, CYP2C9*3 and VKORC1) have been associated with altered metabolism of warfarin, and changes in clinical response [24].…”
Section: Introductionmentioning
confidence: 99%
“…[1,5,17]. For patients like MD, elevated and unstable INR results and challenging warfarin dosing are expected with antiphospholipid syndrome patients [51][52][53][54][55][56][57][58][59][60]. Case reports and one clinical trial have used oral vitamin K doses ranging from 80-500 lg/day [46][47][48][49][50]61].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have defined variable INRs as C3 VKA dose changes or C3 INRs outside the therapeutic range within 6 months or an INR standard deviation [0.5 with C3 warfarin dose changes within 6 months [79,80]. In addition to the aforementioned causes of INR variability, patients with variable INRs have been shown to have a lower daily intake of vitamin K than their counterparts with stable INRs [81].…”
Section: Variable Inrsmentioning
confidence: 99%
“…Another proposed approach is low-dose oral vitamin K supplementation in patients with variable INRs. The ideal dose of supplemental vitamin K is not known, but published studies have used 100-500 lg per day [79,81,83]. In a RCT by Sconce et al [80], patients receiving vitamin K achieved a significantly greater increase in percentage TTR (28% ± 20% vs. 15% ± 20%; P \ 0.01).…”
Section: Variable Inrsmentioning
confidence: 99%